Towards robot cell matrices for agile production – SDU Robotics' assembly cell at the WRC 2018. (17th April 2020) - Schlette, C.; Buch, A. G.; Hagelskjær, F.; Iturrate, I.; Kraft, D.; Kramberger, A.; Lindvig, A. P.; Mathiesen, S.; Petersen, H. G.; Rasmussen, M. H.; Savarimuthu, T. R.; Sloth, C.; et al.
ABSTRACT: To support shifting to high mix/low volume production, manufacturers in high wage countries aim for robotizing their production operations – with a special focus on the late production phases, where robotic assembly cells are then confronted with any complexities resulting from part and product varieties. The 'World Robot Challenge 2018' (WRC 2018) emulated such high mix/low volume production scenarios in a competition taking place in Tokyo, Japan. As part of our activities in SDU's newly founded I4.0 Lab, we integrated and advanced our experiences and developments from our various R & D projects in a novel robotic assembly cell design to compete in the WRC 2018. This article describes the system architecture as well as main aspects of its implementation regarding robot control, robot programming and computer vision and how they contributed to winning the challenge. Due to the application of collaborative robots, the cell design allows for operation without fences. Hence, multiple copies of the cell can be arranged in a highly reconfigurable, highly adaptable matrix structure in which several production flows can be handled concurrently. This concept was demonstrated by the installation of a duplicate cell that allowed for parallel developments on two cells and prolonged development also after shipping the first cell to Japan. GRAPHICAL ABSTRACT: